No Compelling Evidence that Preferences for Facial Masculinity Track Changes in Women's Hormonal Status. (June 2018) - Jones, Benedict C.; Hahn, Amanda C.; Fisher, Claire I.; Wang, Hongyi; Kandrik, Michal; Han, Chengyang; Fasolt, Vanessa; Morrison, Danielle; Lee, Anthony J.; Holzleitner, Iris J.; O'Shea, Kieran J.; Roberts, S. Craig; et al.
Although widely cited as strong evidence that sexual selection has shaped human facial-attractiveness judgments, findings suggesting that women's preferences for masculine characteristics in men's faces are related to women's hormonal status are equivocal and controversial. Consequently, we conducted the largest-ever longitudinal study of the hormonal correlates of women's preferences for facial masculinity ( N = 584). Analyses showed no compelling evidence that preferences for facial masculinity were related to changes in women's salivary steroid hormone levels. Furthermore, both within-subjects and between-subjects comparisons showed no evidence that oral contraceptive use decreased masculinity preferences. However, women generally preferred masculinized over feminized versions of men's faces, particularly when assessing men's attractiveness for short-term, rather than long-term, relationships. Our results do not support the hypothesized link between women's preferences for facial masculinity and their hormonal status.